Research on The Current Situation of Chinese Language Teaching in Kyrgyzstan: 吉尔吉斯斯坦汉语教学现状研究 - Zhypar, Sulaimanova (Mandarinable: Journal of Chinese Studies, 2024)
In today's world, global economic integration is accelerating, and the integration of countries in the political, economic, and cultural fields is further deepening. Language is a communication tool for countries to understand each other and an essential component of international cooperation. Today, learning foreign languages and spreading national languages are increasingly being incorporated into a country's foreign policy strategy, which positively impacts its internal development and helps it expand its influence to other countries. With the increasing popularity of Chinese language and culture abroad, the interest of Kyrgyz citizens in Chinese is also constantly increasing. It is essential to promote Chinese culture and the Chinese language in Kyrgyzstan. The teaching of Chinese in primary and secondary schools and universities in Kyrgyzstan, as well as the work of Confucius Institutes, have provided new impetus and energy for developing cooperation between the two countries. The article analyzes the opportunities and challenges of foreign language and Chinese language teaching in Kyrgyzstan through case analysis, comparative analysis, and literature review. The author concludes that the successful teaching of the Chinese language in education in Kyrgyzstan is inseparable from the political, economic, and cultural support of Kyrgyzstan and its partner countries.